A New Hybrid Technique for Beading and Boxing of Complete Denture Final Impressions - Poonam R Kulkarni; Rahul S Kulkarni; Sumeet Jain (Mashhad University of Medical Sciences, 2017)
Introduction: The purpose of beading & boxing of an impression is to obtain an accurate cast with proper border & base thickness for fabrication of restorations. Beading is the protection of the formed border thickness of the final impressions & Boxing of an impression is building up vertical walls around it. Aim: The purpose of this hybrid technique of beading and boxing is to produce a smooth & aesthetically acceptable cast with accurate border thickness using a simple procedure. Materials & Methods: In this hybrid technique of beading and boxing an impression, a uniform layer of modeling wax was applied over the beading of a plaster-pumice mixture around an impression; after that, boxing & pouring of an impression was done to retrieve a cast. Results: Casts obtained by hybrid technique was more accurate in border thickness & more aesthetic in comparison to the cast obtained by wax technique of beading & boxing. Conclusion: Beading and boxing of an impression is done to protect the formed border thickness of an impression, regulate the height & size of the cast, avoid undue trimming of the cast and to eliminate distortion associated with slumping of the gypsum material when an impression is inverted. This hybrid technique of beading and boxing eliminates the need for applying separating media over the beading of a plaster-pumice mixture and by this technique retrieval of the cast from the impression is very easy and quick. The resulted cast will be very neat and clean with accurate thickness of the borders and base of the cast .This technique is suitable for impressions made from almost any type of impression material.